Response of Strawberry Varieties (Fragaria x ananassa Duch) Produced From Tissue Culture to Amino Acid Terra-Sorb Complex in Some of Physical Properties of Fruits under Unheated Greenhouse Conditions - Hawraa khaleel Sharbak Al-rikabi; AL-zubaidy, Batool (University of Thi-Qar Journal of agricultural research, 2024)
This study was performed in the Agricultural Research Station, affiliated to the College of Agriculture and Marshlands , Thi-Qar University which lies within the longitude (46.22) and latitude (31.05) during the growing season 2023-2024 to study the response of strawberry varieties Fragaria x ananassa Duch ;Monterey, Albion and Rubygem ,produced from tissue culture and sprayed with Terra-Sorb Complex in concentrations of (0, 1, 2, 3) ml.L-1 and their interactions on some of the physical qualities of fruit under unheated plastic house conditions. The experiment was carried out as a factorial experiment using Randomized Complete Block Design (R.C.B.D) and three block (3*3*4) became 36 treatment combinations averages compared to the Least Significant Differences  (L.S.D) at probability level 0.05.Results can be summarized as follows:The fruits of the  variety Albion showed a moral superiority in the number of fruits reaching (11.77 fruit.plant-1) comparison with variety Monterey register (9.72 fruit.plant-1 )and  the length and diameter of the fruit moral superiority (39.74 , 32.64) mm compared to the Monterey variety that they registered (33.06 , 26.79) mm respectively variety record Albion also morally superior fruit size record (14.59 cm3) while variety Rubygem highly morally outweighed by the average tender weight of fruits reaching (83.74 g.plant-1) comparison with variety Monterey record (74.88 g.plant-1).The spraying of  Terra-Sorb Complex  plants leads to a high morale increase as the spraying exceeds the concentration of 3 ml.L-1 in high spirits record highest average number of fruits reached (12.29 fruit.plant-1) for comparison treatment the comparison reaching (8.81 fruit.plant-1 )the length and diameter of the fruit reached (46.24 ,37.51) mm measured by comparison treatment (28.04 ,22.88) mm its size reached (16.39 cm3) measure by comparison treatment reached (10.74 cm3) The tender weight of the fruit has reached (97.82 g.plant-1) measure by comparison treatment (58.37 g.plant-1).Results showed the overlap between the variety and the spraying by Terra-Sorb Complex a clear high-morale effect on the profiled qualities as Albion class overlap outweighs by concentration 3 ml.L-1 with remarkable morale in fruit preaching, fruit length, fruit diameter and fruit size and the tender weight of fruits reaching (13.55 fruit.plant-1, 50.48 mm, 44.48mm, 18.63 cm3,99.63 g.plant-1) respectively.